Inventory Effectiveness and Nigeria Manufacturing Companies: Analysis with Return on Equity - Tajudeen Adegbite; Surajdeen Ajagbe (Iranian Journal of Accounting, Auditing & Finance)
This study examined the impact of inventory management on the profitability of selected manufacturing companies in Nigeria. Specifically, the study determined the effect of inventory management on return on equity.  The data were sourced from annual published reports of ten selected companies. The data sourced were inventory, asset, revenue, equity, turnover, and profit after tax. The data collected were analyzed with panel data using random effect, fixed effect, regression, and correlation. The result showed that return on equity has a good correlation with inventory. Also, it was discovered from the analysis that according to the Fixed effect result, inventory positively affects return on equity. Still, the asset has a negative effect on Profitability. Turnover and equity have a significant positive effect on return on equity. Conclusively, inventory positively impacts return on equity in Nigerian manufacturing companies. It recommended that Nigerian manufacturing companies should not trivialize inventories but put more effort into the management of inventory so that the profitability of the company will be efficiently enhanced and increased at an increasing rate so that investors’ investment will be multiplied because rational investors discard unproductive company to accept the profitable companies.